An Evaluation Method of Urban Public Transport Facilities Resource Supply Based on Accessibility. (29th October 2018) - Sun, Chao; Chen, Xiaohong; Zhang, H. Michael; Huang, Ze
Abstract : The two indices of the supply level of urban public transport facilities resource and the public transport-private cars traveling time ratio are used to evaluate the public transport accessibility in urban networks. An evaluation method for urban public transport facilities resource supply is proposed based on accessibility by taking Shenzhen as the research area and by using the London PTAL evaluation system. The method takes into account the walking time outside the public transit station and the spatial layout of public transit stations, reflects regional development opportunity, and can reflect regional differences regarding public transport facilities resources in various spatial scales. This paper evaluates the relative service competiveness of public transports and private cars in the entire travel of individuals based on the public transport-private cars travelling time ratio, which lays a foundation to judge the service level of public transport and to make a purpose-specific transportation policy and public transport development scheme.